Photocontrol of Axillary Bud Outgrowth by MicroRNAs: Current State-of-the-Art and Novel Perspectives Gained From the Rosebush Model - Mallet, Julie; Laufs, Patrick; Leduc, Nathalie; Le Gourrierec, José (Frontiers in Plant Science, 2022)
Shoot branching is highly dependent on environmental factors. While many species show some light dependence for branching, the rosebush shows a strict requirement for light to allow branching, making this species an excellent model to further understand how light impinges on branching. Here, in the first part, we provide a review of the current understanding of how light may modulate the complex regulatory network of endogenous factors like hormones (SL, IAA, CK, GA, ABA), nutrients (sugar, nitrogen) and ROS to control branching. We review the regulatory contribution of miRNAs to branching in different species, highlighting the action of such evolutionarily conserved factors. We underline some possible pathways by which light may modulate miRNA-dependant regulation of branching. In the second part, we exploit the strict light dependence of rosebush for branching to identify putative miRNAs that could contribute to the photocontrol of branching. For this, we first performed a profiling of the miRNAs expressed in early light-induced rosebush buds and next tested whether they were predicted to target recognized regulators of branching. Thus, we identified seven miRNAs (miR156, miR159, miR164, miR166, miR399, miR477, miR8175) that could target nine genes (CKX1/6, EXPA3, MAX4, CYCD3;1, SUSY, 6PFK, APX1, RBOHB1). Because these genes are affecting branching through different hormonal or metabolic pathways and because expression of some of these genes is photoregulated, our bioinformatic analysis suggests that miRNAs may trigger a rearrangement of the regulatory network to modulate branching in response to light environment.